Current Status of the Long-term Care Security System for Older Adults in China. (March 2021) - Du, Peng; Dong, Tingyue; Ji, Jingyao
In response to the increasing care demand of older adults and their families, the construction of the long-term care (LTC) security system has been widely recognized by the government, society and families. This article discusses the socio-demographic background, current situation, achievements and issues of this system. The LTC security system in China has achieved considerable progress in enriched service provision and expanded social insurance system pilot programs. However, the issues of unbalanced service provision and the explorative design of the insurance system still need to be resolved. Our recommendations for the development of the LTC security system include comprehensively reviewing the integrated care service system in terms of placing "old adults at the center, " addressing the long-standing divisions between urban and rural areas in service provision and insurance design, advancing research and discussion concerning pilot experiences and improving the unified evaluation and financial planning systems.